2006
DOI: 10.1007/s00439-006-0238-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential effect on cellular response to cadmium of a single-nucleotide A → G polymorphism in the promoter of the human gene for metallothionein IIA

Abstract: Most people generally ingest cadmium in their food. Cadmium that has accumulated in tissues induces the synthesis of metallothioneins (MTs) which are metal-binding proteins that bind tightly to cadmium to inhibit its renal toxicity. Individuals whose ability to induce the synthesis of MTs is low seem likely to be particularly susceptible to the toxic effects of cadmium. In this study, we analyzed the polymorphism of the promoter region of the gene for MT-IIA, the major species of MT in humans, in 119 adult Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 25 publications
4
34
2
Order By: Relevance
“…The genotypes of A/A, A/G, and G/G accounted for 98 (82.4%), 20 (16.8%), and 1 (0.8%) of them, respectively. We also confirmed that the A G SNP significantly reduced cadmium-induced transcription of the metallothionein-2A gene 72) , suggesting that although only one of our study participants had the G/G type, people with this genotype might be more sensitive to cadmium toxicity than those with the A/A type, because of a limited ability to induce metallothionein synthesis. Workers with the metallothionein-2A G/G genotype (perhaps also the A/G type) who work in industries that handle cadmium might be prone to developing various biological dysfunctions when exposed to cadmium, because cadmium affects various biological processes (see Discussion).…”
Section: -C Of Yoshida's Report) 30) This Indicates That Some Indivsupporting
confidence: 77%
See 1 more Smart Citation
“…The genotypes of A/A, A/G, and G/G accounted for 98 (82.4%), 20 (16.8%), and 1 (0.8%) of them, respectively. We also confirmed that the A G SNP significantly reduced cadmium-induced transcription of the metallothionein-2A gene 72) , suggesting that although only one of our study participants had the G/G type, people with this genotype might be more sensitive to cadmium toxicity than those with the A/A type, because of a limited ability to induce metallothionein synthesis. Workers with the metallothionein-2A G/G genotype (perhaps also the A/G type) who work in industries that handle cadmium might be prone to developing various biological dysfunctions when exposed to cadmium, because cadmium affects various biological processes (see Discussion).…”
Section: -C Of Yoshida's Report) 30) This Indicates That Some Indivsupporting
confidence: 77%
“…Since cadmium induces metallothionein synthesis at the transcriptional level, we analyzed genetic polymorphisms of the region around the transcriptional start site (a known promoter region) of the metallothionein-2A gene, the main isoform of human metallothionein genes 72) . We isolated DNA from blood samples provided by 119 Japanese individuals and used PCR to amplify a 222-base pair (bp) fragment located 202 bp upstream and 20 bp downstream of the transcription start site.…”
Section: -C Of Yoshida's Report) 30) This Indicates That Some Indivmentioning
confidence: 99%
“…It has been shown that the -5 A/G SNP in the MT2A reduces the eYciency of the induction of gene transcription by heavy metals (Kita et al 2006), whereupon lack of metallothionein gene expression makes the organism more sensitive to the toxic eVects of heavy metals (Nordberg 1998). In previous studies, it was found that the core promoter region polymorphism of metallothionein 2A increases the accumulation of Cd in human renal cortex , and the eVects of metallothionein 2A polymorphism on placental cadmium accumulation were shown (Tekin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a later study examining DNA isolated from leukocytes, a single-nucleotide polymorphism in the promoter region of the methallothionein-IIA gene was found in 18% of 119 Japanese subjects (Kita et al 2006). HEK293 cells expressing this single-nucleotide polymorphism had significantly decreased metallothionein expression in the presence of Cd (Kita et al 2006). Interestingly, Yoshida et al (1998) reported that there was no correlation between low metallothionein expression and renal-related cause of death or any signs of overt, renal pathology.…”
Section: Early Systemic Markers Of CD Toxicitymentioning
confidence: 91%
“…One explanation for this may be genetic differences in the promoter region of the methallothionein gene. In a later study examining DNA isolated from leukocytes, a single-nucleotide polymorphism in the promoter region of the methallothionein-IIA gene was found in 18% of 119 Japanese subjects (Kita et al 2006). HEK293 cells expressing this single-nucleotide polymorphism had significantly decreased metallothionein expression in the presence of Cd (Kita et al 2006).…”
Section: Early Systemic Markers Of CD Toxicitymentioning
confidence: 95%